Fungsi Inovasi Pendidikan dalam Pembelajaran Berbasis Teknologi Digital Di SD N 069 VII Sungai Gedang - Ahmad Ridwan; Izalmianto Izalmianto; Thoriq Kurniawan; Wildan Ahmad Rauf; Akhmad Arifin (Elkom: Jurnal Elektronika dan Komputer, 2024)
This research uses a literature study, a descriptive qualitative research type, a literature review describing the function of digital technology-based learning educational innovation. Research uses written sources such as articles, journals and relevant documents. The literature study focuses on the function or role of educational innovation, educational digital technology, and the use of educational technology. The study results show innovation in the process of renewal and change. Innovation is very necessary in the world of education so that it continues to develop. The use of technology has positive and negative impacts. The impact generated is focused on positive things and minimizes negative impacts if there is good cooperation from various parties so that the use of technology meets its objectives. The function of educational innovation in digital technology-based learning is very important. So that the use of digital technology can be carried out optimally and comprehensively, good innovation needed.